Determinants of financial distress: the role of liquidity, profitability, leverage, and firm size - Siti Aisyah Akashi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
This title was chosen because financial distress awareness can help management practices navigate risks that threaten a firm’s economic health. The analysis was conducted in the transportation & logistics sector of the Indonesia Stock Exchange, considering that the arrival of COVID-19 suppressed community mobility, resulting in a decrease in revenue and operating profit for companies in the sector. This research employed an associative quantitative method to analyze the secondary data collected. The research population comes from companies listed in the transportation & logistics sector of the Indonesia Stock Exchange. The sampling technique employed was a purposive sampling method, yielding 98 research samples. The analysis method used here is a pooled cross-section, which is assisted by Microsoft Excel and Eviews 13 tools. The results of this study state that Liquidity has a significant effect on Financial Distress; Profitability has no considerable effect on Financial Distress; Leverage has no significant impact on Financial Distress; and Company Size has no considerable effect on Financial Distress in companies listed in the transportation and logistics sector on the Indonesia Stock Exchange for the period 2019-2022.